Increasing transmission of electronic interaction in dinuclear unsymmetric mixed-valent ruthenium complexes - Fagalde, Florencia (2007)
The preparation and characterization by spectroscopic and electrochemical techniques of new dinuclear complexes of the type [(tpm)(bpy)RuII(L)RuII/III(NH3)5]4+/5+ (bpy =2,2'-bipyridine, tpm = tris(1-pyrazolyl)methane, L = pz (pyrazine), 4,4´-bpy (4,4´-bipyridine), BPE (trans-1,2-bis(4-pyridyl)ethylene) and PCA (= 4- pyridinecarboxaldehide azine), are described in this work. The analysis of the visible spectral data for the metal-to-metal charge transfer (MMCT) bands in the corresponding mixed-valent species [RubII,RuaIII] (Rub = Ru bonded to bpy; Rua = Ru bonded to NH3) allows the determination of the reorganization energies l and electronic coupling elements HAB for the intramolecular electron transfers Rub II -Rua III mediated by L. An increased transmission of the metal-to-metal electronic interaction is disclosed for this series, when comparing the distance dependence of HAB to that of the analogous series with trpy (2,2':6',2"-terpyridine) acting as a spectator ligand instead of tpm.